Find the center of gravity of the two joined beams. Express your answer in the form x,y, taking the origin at the corner where the beams join.

Respuesta :

Answer:

Xcg = 0.5476 m

Ycg = 0.2262 m

Step-by-step explanation:

We can apply the Equations :

Xcg= (x₁*m₁ + x₂*m₂) / (m₁ + m₂)

Ycg= (y₁*m₁ + y₂*m₂) / (m₁ + m₂)

Given

m₁ = 19.00 Kg

x₁ = 0.00 m

y₁ = 0.50 m

m₂ = 23.00 Kg

x₂ = 1.00 m

y₂ = 0.00 m

then we apply

Xcg = (0.00 m*19.00 Kg + 1.00 m*23.00 Kg) / (19.00 Kg + 23.00 Kg)

Xcg = 0.5476 m

Ycg= (0.50 m*19.00 Kg + 0.00 m*23.00 Kg) / (19.00 Kg + 23.00 Kg)

Ycg = 0.2262 m

We can see the beams in the pic.

Ver imagen jolis1796
ACCESS MORE